Efficacy of D‐cycloserine augmented brief intensive cognitive‐behavioural therapy for paediatric obsessive‐compulsive disorder: A randomised clinical trial. Issue 6 (27th January 2022) - Farrell, Lara J.; Waters, Allison M.; Tiralongo, Evelin; Mathieu, Sharna; McKenzie, Matthew; Garbharran, Vinay; Ware, Robert S.; Zimmer‐Gembeck, Melanie J.; McConnell, Harry; Lavell, Cassie; Cadman, Jacinda; Ollendick, Thomas H.; et al.
Abstract: Objective: To examine the efficacy of weight‐adjusted D‐cycloserine (DCS) (35 or 70 mg) relative to placebo augmentation of intensive exposure therapy for youth with obsessive‐compulsive disorder (OCD) in a double‐blind, randomised controlled trial, and examine whether antidepressant medication or patient age moderated outcomes. Methods: Youth ( n = 100, 7–17 years) with OCD were randomised in a 1:1 ratio to either DCS + exposure ( n = 49) or placebo + exposure ( n = 51). Assessments occurred posttreatment, 1 month later, and at 3 and 6 months. Pills were ingested immediately before sessions. Results: Significant improvements on all outcomes were observed at posttreatment, and to 6‐month follow‐up. Treatment arms did not differ across time, with no significant time‐by‐medication interactions on symptom severity (T1 to T2 estimate: 9.3, 95% confidence interval [CI]: −11.2 to −7.4, and estimate −10.7, 95% CI: −12.6 to −8.7), diagnostic severity (T1 to T2 estimate: −2.0, 95% CI: −2.4 to −1.5 and estimate −2.5, 95% CI: −3.0 to −2.0) or global functioning (T1 to T2 estimate: 13.8, 95% CI: 10.6 to 17.0, and estimate 16.6, 95% CI: 13.2 to 19.9). Neither antidepressants at baseline nor age moderated primary outcomes. There were significantly fewer responders/remitters at 1‐ and 6‐month follow‐up among youth in the DCS condition stabilised on SSRIs, relative to youth not taking SSRIs. Conclusions: DCS augmented intensive exposure therapy did not result in overall additional benefits relative to placebo. Intensive exposure proved effective in reducing symptoms for the overall sample.